MANAJEMEN PELAYANAN PEMBUATAN PASPOR PADA KANTOR IMIGRASI KELAS II TPI MERAUKE - Andri Irawan; Marten Z Jamlean; Hendro Ibrahim (Madani Jurnal Politik dan Sosial Kemasyarakatan, 2022)
The standard of public service for the Class II TPI Merauke Immigration Office in providing passport-making services, the procedure for making passports for the Class II TPI Merauke Immigration Office is currently said to be good and in accordance with the SOP. The completion time for making passports takes a maximum of 3 (three) days but at the Class II Immigration Office of TPI Merauke there is an innovation so it is only 2 (two) days. Regarding the cost of services provided by the Immigration Office to applicants (community), passport makers are sufficient to fulfill because passports are indeed important things that are urgently needed by applicants (community) to travel abroad, which is Rp. 350,000 for a 48 page passport. Facilities and infrastructure have also been very supportive in the needs of making passports. Likewise, the competence of officers in providing services is good. Factors that affect the process of making passport services at the Immigration Office Class II TPI Merauke. These factors consist of supporting factors such as office infrastructure and innovations. Meanwhile, the inhibiting factor is public awareness, lack of public awareness in completing files so that services cannot be carried out are the main triggers because people are less aware that in passport processing it is necessary to prepare to complete the necessary files.